On the Multifractal Features of Low‐Frequency Magnetic Field Fluctuations in the Field‐Aligned Current Ionospheric Polar Regions: Swarm Observations. Issue 5 (29th April 2020) - Consolini, G.; De Michelis, P.; Alberti, T.; Giannattasio, F.; Coco, I.; Tozzi, R.; Chang, T. T. S.
Abstract: Recent findings on the nature of magnetic field fluctuations in the high‐latitude ionospheric regions have suggested the existence of scaling features, which are the signature of the occurrence of turbulence. These features mainly characterize the magnetic field fluctuations in those regions where the field‐aligned currents flow. Here, we investigate the nature of the Earth's magnetic field fluctuations using the high‐resolution (50 Hz) magnetic measurements from the European Space Agency Earth's observation mission Swarm. Our study indicates that spatiotemporal anomalous scaling features characterize low‐frequency magnetic field fluctuations in the high‐latitude ionospheric regions of field‐aligned currents at spatial scales in the range 0.8–80 km (timescales in the range 0.1–10 s). The signature of a multifractal nature of these fluctuations suggests a highly complex structure of the field‐aligned currents. Our results support the view of inhomogeneous (filamentary) field‐aligned currents, which can have relevant implications in the comprehension of the physical processes responsible for the magnetospheric‐ionospheric coupling and ionospheric heating. Key Points: Low‐frequency magnetic field fluctuations in the topside F region polar ionosphere show scale‐invariance Anomalous scaling (multifractal/intermittent) features and anisotropy of magnetic field fluctuations are studied A link between the scale‐invariance of fluctuations and the filamentary nature of field‐aligned currents is discussed